The relationship on literacy with acceptance towards GST implementation in Johor / Siti Syaqilah Hambali - Hambali, Siti Syaqilah (2015)
GST implementation in Malaysia in April 2015 is part of the tax reformation with the goal of having a more efficient and effective taxation system. A successful tax reformation requires a high acceptance from taxpayers. In order to assist in the acceptance of GST implementation in Malaysia, taxpayers need to have a proper knowledge and awareness of the GST system, also known as GST literacy. Thus, this study aims to assess the level of GST literacy of secondary school teachers as well as examining their GST-acceptance level towards GST implementation in Malaysia. This study determines the GST literacy level from the perspective of GST knowledge and GST awareness. Apart from that, this study is also aim to identify the relationship between GST literacy levels with the GST acceptance levels of secondary school teachers. Questionnaires were distributed to 150 secondary school teachers in Batu Pahat, Johor and the response rate was 66.67%. The finding indicates secondary school teachers as literate towards the GST implementation in Malaysia. The findings also suggest that secondary school teachers have a moderate knowledge level and high awareness level on GST implementation in Malaysia. The study proves statistically that there is a positive significant relationship between GST literacy with GST acceptance. The results suggest that government should provide sufficient information and explanation of GST implementation through various ways such as media social, distribution of pamphlets, publish of articles, TV talks on GST, and whatnot . This is due to the fact that sufficient information can increase the literacy level of taxpayers.